Inconsistencies and Beyond. A Logical-Philosophical Discussion - Batens, Diderik (Revue Internationale de Philosophie, 1997)
The paper starts off by epistemological arguments for the need of paraconsistent logics. Next it is argued that some contexts require that one allows for other abnormalities, next to or instead of inconsistencies. The feasibility of such moves is defended in terms of a contextual epistemology. Finally, adaptive logics are defended as means to interpret theories `as normally as possible', even if they contain some abnormalities.